Growth of Yearling Heifers under Different Systems of Grazing on Cenchr Us - Eleusine - Aristida Pasture in Arid Region - Rathore, S S (Annals of Arid Zone, 2016)
Annual variations in body weight gain of yearling heifers (breed Nagauri) on Cenchrus - Eleusine - Aristida dominated range-land (1.2 ha/heifer) ranged from 305 to 41.0 kg/animal in continuous grazing and 52.21 to 59.58 kg/ animal in deferred rotational grazing in arid western Rajasthan. Seasonal qualitative variation of the forage influenced the seasonal body weight gain. Weight gain was maximum during September - October and minimum during March - April.